Scaphoid non-union in osteogenesis imperfecta. (11th January 2016) - Pinder, Elizabeth; Fok, Jonathan; Crossman, Paul
Abstract : We report a case of scaphoid non-union in a child with osteogenesis imperfecta (OI) presenting 7 months after a fall. Following diagnosis, conservative treatment was initiated, but despite 4 months in a plaster cast, the fracture had failed to unite. Open reduction and internal fixation was performed (Acutrak screw) with bone graft harvested from the distal radius. Postoperative immobilisation continued for 10 weeks, and at 4 months the child was pain free and had resumed normal activities. The fracture had fully united radiologically at 9 months. Non-union is reported to occur in 23% of paediatric scaphoid fractures when treatment is delayed, and conservative and surgical treatment have both been described. Since OI increases the risk of non-union in long bone fractures, the scaphoid may also be at risk. We recommend a high level of suspicion for non-union in this patient group and a low threshold for consideration of surgical treatment.